The Influence of Logistic Service Quality on Customer Satisfaction: The Moderating Role of Environmental Friendliness - Arif Rohman Khakim; Wahyuningsih Santosa; Triwulandari Satitidjati Dewayana; Kunto Bagas Koro (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aimed to investigate how key dimensions of logistics service quality, including timeliness, reliability, condition of goods upon delivery, flexibility, and responsiveness, affect customer satisfaction. This study also examines the moderating role of environmental friendliness in the relationship between logistics service quality and customer satisfaction. Methodology: This study adopted a quantitative approach and used purposive sampling to select 153 respondents who were active users of e-commerce platforms in Jabodetabek. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) via SmartPLS 4. Results: The results show that timeliness, reliability, and condition of goods significantly influence customer satisfaction, whereas flexibility and responsiveness do not. Environmental friendliness moderates only the effect of the condition of goods; other moderating effects are not significant. Conclusions: Although sustainable practices are becoming increasingly important, logistics service quality remains the primary driver of customer satisfaction. Environmental friendliness has a limited moderating role, underscoring the continued relevance of core service quality. Limitations: This study is limited to e-commerce consumers in Jabodetabek, and an incomplete measurement of environmental friendliness restricts the generalizability of the findings. Contributions: This research contributes to logistics management practitioners and academics in logistics operations management, particularly within Indonesia’s e-commerce industry.